Unpacking the Relationship among Task Engagement, Achievement Emotions and Emotion Regulation among EFL Learners: A Network Analysis. - Jiang, Anne Li; Sun, Ke; Liang, Junjian; Jin, Yidan; Zhang, Suju (Perceptual & Motor Skills, 2025)
In this study, drawing on an integrated understanding of the process model of emotion regulation (Gross, 2015) and the control-value theory (Pekrun, 2006), and informed by principles from the complex dynamic systems theory, we used a network analysis to examine the relationships between task engagement, achievement emotions (i.e., enjoyment, boredom and anxiety), and emotion regulation of 348 Chinese college students in English-as-a-foreign language (EFL) classes. We found a relatively strong connection between these constructs, with cognitive appraisal, enjoyment, and emotional engagement being the most central nodes within connections to task engagement, achievement emotions, and emotion regulation, respectively. Notably, strong peripheral relationships emerged between enjoyment and all facets of task engagement, all of which were positively associated with cognitive reappraisal but negatively with boredom. Expressive suppression was positively linked only with boredom and anxiety, whereas cognitive reappraisal was positively associated with social engagement. We found no direct association between task engagement and anxiety or emotion suppression. Collectively, these findings provide novel insights into the emotional underpinnings of students' task engagement in EFL contexts.